Reward and Punishment Mediation in the Relationship Between Employee Discipline, Communication, and Employee Commitment - Krisna Ramadhan Budiarto; Andi Indrawati; Rusmadi Wongso (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
In the context of public-sector organizations facing increasing demands for accountability and performance, understanding the mechanisms that shape employee commitment remains a critical managerial concern. This study examines the mediating roles of reward and punishment in the relationships among employee discipline, communication, and employee commitment. Using a quantitative approach with Structural Equation Modeling (SEM), data were collected from all 130 employees through total sampling. The findings indicate that employee discipline significantly influences employee commitment but has no significant effect on communication. Reward and punishment significantly improve communication, but do not enhance employee commitment. Mediation tests show that reward and punishment do not significantly mediate the relationship between discipline and employee commitment, although partial mediation occurs in the discipline–communication pathway. This study concludes that employee commitment in public-sector organizations cannot be effectively developed solely through extrinsic control mechanisms. This research contributes to public-sector HRM literature by demonstrating that structured reinforcement systems strengthen communication yet fail to build deeper psychological commitment.